1984
DOI: 10.1088/0029-5515/24/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Energy confinement of beam-heated divertor and limiter discharges in Doublet III

Abstract: Observation of the intensity of the recycling particle flux at the main plasma edge for various limiter and divertor discharges indicates that the gross energy confinement of beam-heated discharges is closely related to the intensity of the edge particle flux. In limiter discharges, the global particle confinement time and the energy confinement time τE show many similarities: 1) linear Ip dependence at Ip < 600 kA, 2) no BT dependence, and 3) deterioration against injection power. Improvement of τE by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…Doublet III followed shortly thereafter [34] confirming the lower power threshold in deuterium. In 1985, JET demonstrated that the H-mode could also be realised in the worldwide largest tokamak [35].…”
Section: The H-mode Of Asdex [23-25]mentioning
confidence: 70%
“…Doublet III followed shortly thereafter [34] confirming the lower power threshold in deuterium. In 1985, JET demonstrated that the H-mode could also be realised in the worldwide largest tokamak [35].…”
Section: The H-mode Of Asdex [23-25]mentioning
confidence: 70%
“…In their expanded boundary configuration, both the JAERI and GA teams on D-III attained the H-mode, 41 ' 59~61 but their details differed from those of ASDEX and PDX. For instance, no sharp transition into the H-mode was observed during NBI; improved energy confinement was observed from the outset of NBI, and even, in some cases, in the ohmic plasma.…”
Section: Second Generation Experimehts (H- 2- and P-modes)mentioning
confidence: 99%
“…Impurities found in the main plasma are derived from interaction of the SOL plasma with the limiter and other vacuum vessel components. There is also experimental evidence that plasma near the boundary (defined by the limiter or separatrix radius, r «* a) can strongly affect the global energy confinement time (H-mode) [1][2][3]. Furthermore, the parameters of the SOL plasma reflect the heat and particle fluxes originating from r ^ a, an area which is generally difficult to diagnose by direct means.…”
Section: Introductionmentioning
confidence: 99%